THE HISTORY OF KARAKALPAK FOLK PEDAGOGY FORMATION AND PEDAGOGICAL FOUNDATIONS OF MORAL EDUCATION OF STUDENTS - Esemuratova, Turganbike Aytmuratovna (SCIENCE and SOCIETY, 2026)
This article examines the formation of Karakalpak folk pedagogy, its historical foundations, its role within the system of national values, and its significance in the moral education of students. It also analyzes the pedagogical potential of folklore, customs, traditions, and national values in fostering morality, diligence, patriotism, humanism, and the spiritual development of the younger generation.